2022
DOI: 10.1172/jci.insight.154194
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cell–derived IL-13 increases macrophage IL-10 to resolve neuropathic pain

Abstract: Understanding the endogenous mechanisms regulating resolution of pain may identify novel targets for treatment of chronic pain. Resolution of chemotherapy-induced peripheral neuropathy (CIPN) after treatment completion depends on CD8 + T cells and on IL-10 produced by other cells. Using Rag2 –/– mice lacking T and B cells and adoptive transfer of Il13 –/– CD8 + T cells, we showed that CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In addition, it can act as an analgesic by stimulating macrophages to produce the analgesic factor IL-10. 14 However, more in-depth studies on its analgesic properties are yet to be detected. Both IL-4 and IL-13 have analgesic effects, so we hypothesized that when dupilumab antagonized IL-4Rα and thus inhibited the IL-4, and IL-13 pathway, the skin showed pain sensitivity especially in the lesions that were improving because the barrier was being reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can act as an analgesic by stimulating macrophages to produce the analgesic factor IL-10. 14 However, more in-depth studies on its analgesic properties are yet to be detected. Both IL-4 and IL-13 have analgesic effects, so we hypothesized that when dupilumab antagonized IL-4Rα and thus inhibited the IL-4, and IL-13 pathway, the skin showed pain sensitivity especially in the lesions that were improving because the barrier was being reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study using the same model showed that T cells likely play a more important role in promoting neuropathic pain in female mice than in male mice [55]. Since this time, it has become clear that the type of T cell is critical for understanding the impact of these cells on neuropathic pain and neuropathic pain resolution [52]. Another potential reason for this difference in the duration of effect is that the SNI model creates a situation where nociceptor spontaneous activity is continuously driven by the ligation injury to the injured nerves.…”
Section: Discussionmentioning
confidence: 99%
“…(Basso et al, 2015 ; Swain et al, 2022 ). Recent studies have found that T cells are also involved in neuropathic pain: CD8 + T cells and endogenous IL-10 are required to resolve chemotherapy-induced neuropathic pain (Krukowski et al, 2016 ); educating CD8 + T cells can prevent and resolve chemotherapy-induced peripheral neuropathy in mice (Laumet et al, 2019 ; Singh et al, 2022 ). Intriguingly, in the bone cancer pain model which may involve both inflammatory pain and neuropathic pain, systemic administration of STING activator DMXAA attenuated the measures of spontaneous and ongoing pain; the analgesic effect may attribute to the increasing proportion of CD8 + T cells in the bone marrow tumor microenvironment (Donnelly et al, 2021 ).…”
Section: The Potential Mechanism Of the Cgas-sting Pathway In Chronic...mentioning
confidence: 99%